Single-shot attenuation coefficient estimation for ultrasound contrast agents - Birdi, Jasleen; Heymans, Sophie V.; Collado-Lara, Gonzalo; Van Den Abeele, Koen; D’hooge, Jan; Bertrand, Alexander (Frontiers in Physics, 2022)
Ultrasound contrast agents (UCAs) have broadened the scope of ultrasound imaging and therapeutic applications. One of the parameters of interest when measuring the response of UCAs to ultrasound is their frequency-dependent attenuation coefficient. The estimation of this parameter is relevant for sensing and therapeutic applications, as well as for obtaining the viscoelastic properties of the UCA's shell. The current practice to obtain this coefficient relies on experimental measurements made both in the presence and absence of UCAs in a target medium. Not only is the microbubble-free reference measurement time-consuming, but it may also not always be feasible for in-vivo applications due to lack of an appropriate reflector. To overcome these challenges, we present here a novel approach which estimates the UCA's attenuation spectra directly from pulse-echo measurements made in the underlying UCA medium, without any reference measurement. Furthermore, despite the non-linear frequency dependency of the UCA's attenuation profile, our approach can still benefit from a fast linear least-squares based estimation scheme, providing attenuation estimates in a single-shot, which is desirable for implementation in real-time systems. We provide an investigative study, testing the estimator's performance on various simulated realistic attenuation profiles obtained by varying the shell parameters and the UCA's size distribution. In all cases, the estimated attenuation profiles were in good agreement with the true ones, with a relative error < 10%. Evaluation on experimental in-vitro data shows a relative error < 15%, which further highlights the potential of our approach for fast and accurate UCA's attenuation estimation.